2015
DOI: 10.1021/acsami.5b00306
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Adsorption on Amine-Functionalized Periodic Mesoporous Benzenesilicas

Abstract: CO2 adsorption was investigated on amine-functionalized mesoporous silica (SBA-15) and periodic mesoporous organosilica (PMO) samples. Hexagonally (p6mm) ordered mesoporous SBA-15 and benzene-PMO (BPMO) samples were prepared in the presence of Pluronic P123 block copolymer template under acidic conditions. Three kinds of amine-containing organosilanes and polyethylenimine were used to functionalize SBA-15 and BPMO. Small-angle X-ray scattering and nitrogen adsorption isotherms showed that these samples feature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
65
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 99 publications
(69 citation statements)
references
References 43 publications
0
65
1
Order By: Relevance
“…Recently, alkyl amine functionalities (more specifically the N- [3-(trimethoxysilyl)propyl]-ethylenediamine) grafted on the silanols of phenylene-bridged PMO and of SBA-15 were tested in the adsorption of pure CO2 at 25 °C in a pressure range up to 1.2 atm. 38 It was observed that the alkyl amine-PMO adsorbs a larger amount of CO2 at a faster adsorption rate when compared with SBA-15, which demonstrates that the functionalization of PMOs with amines is more relevant than a similar degree and nature of functionalization in silica for the adsorption of CO2. Interestingly, the unmodified SBA-15 silica also adsorbs a smaller amount of CO2 when compared with the unmodified PMO.…”
mentioning
confidence: 91%
“…Recently, alkyl amine functionalities (more specifically the N- [3-(trimethoxysilyl)propyl]-ethylenediamine) grafted on the silanols of phenylene-bridged PMO and of SBA-15 were tested in the adsorption of pure CO2 at 25 °C in a pressure range up to 1.2 atm. 38 It was observed that the alkyl amine-PMO adsorbs a larger amount of CO2 at a faster adsorption rate when compared with SBA-15, which demonstrates that the functionalization of PMOs with amines is more relevant than a similar degree and nature of functionalization in silica for the adsorption of CO2. Interestingly, the unmodified SBA-15 silica also adsorbs a smaller amount of CO2 when compared with the unmodified PMO.…”
mentioning
confidence: 91%
“…[14] Furthermore,t he surface of carbon quantum dots is easily functionalized by amino groups (ÀNH 2 ), which can increase the CO 2 adsorption ability efficiently. [14,15] Al arge CO 2 adsorption capacity is facile to enhance the activity for electrochemical reduction of CO 2 .B ecause of the large number of amino groups on the surface,n itrogen-doped graphene quantum dots (NGQDs) are promising efficient electrocatalysts for CO 2 reduction. [8c] Based on the above analysis results,itisreasonable to assume that the composite electrocatalysts composed of NGQDs and Bi 2 O 3 nanosheet can effectively catalyze the electrochemical reduction of CO 2 .…”
mentioning
confidence: 99%
“…[1a,11b,17] However,l ike most catalysts,t he formate FE decreases rapidly at more negative potentials than the optimum potential (a potential for achieving the largest FE). [14,15,19] Consequently,wespeculate that ahigh formate FE at more negative potentials is attributed to the enhanced adsorption capacity of adsorbed CO 2 and OCHO* intermediate.F or most catalysts, the weak adsorption energy of adsorbate results in an insufficient concentration of CO 2 (ads) and reaction intermediates on the catalysts surface for reaction consumption at more negative potentials,w hich leads to CO 2 reduction reactions reaching the mass transfer limit. Obviously,t he introduction of NGQDs significantly enhanced the activity for SnO 2 -NGQDs over awide negative potential range (À0.9 VtoÀ1.3 V).…”
mentioning
confidence: 99%
“…Table shows that the amine contents for XAD‐4‐DETA, XAD‐4‐TETA, and XAD‐4‐TEPA are 4.19, 4.69, and 5.15 mmol/g, respectively. On the basis of the Kyohyun Sim mechanism, a higher amine group content of the adsorbent could lead to higher CO 2 adsorption capacity. However, an excess content of amine may block the pores of XAD‐4, which limits the further inner diffusion of CO 2 and ultimately reduces the accessibility of CO 2 molecules to the internal amine groups.…”
Section: Resultsmentioning
confidence: 99%
“…23 Thus, the amine content was a significant influential factor for CO 2 capture. 24 a higher amine group content of the adsorbent could lead to higher CO 2 adsorption capacity. However, an excess content of amine may block the pores of XAD-4, which limits the further inner diffusion of CO 2 and ultimately reduces the accessibility of CO 2 molecules to the internal amine groups.…”
Section: Resultsmentioning
confidence: 99%